Application of GPR Survey in the Investigation of a Plane Crash from the Second World War - Pasterkiewicz, Wojciech; Rajchel, Bernadeta (Analecta Archaeologica Ressoviensia, 2017)
The article discusses the use of a ground-penetrating radar (GPR) for locating objects originating from the war period. It also presents the results of GPR research, showing the presence of a World War II aircraft wreck located in the subsurface layer in Krościenko Wyżne, Krosno County, Podkarpackie Voivodeship. Excavations carried out later have confirmed these surveys. The remains of the aircraft were documented in spots in which anomalies were indicated by the GPR. The conducted archaeological work made it possible to assess the effectiveness of the georadar technique.